Characterization of Aerococcus viridans Isolates from Swine Clinical Specimens - Martín, V. (American Society for Microbiology, 2007)
We present here the biochemical and genetic characterization and antimicrobial susceptibility of 58 isolates of Aerococcus viridans isolated in pure culture from different clinical specimens of normally sterile body sites of pigs. A. viridans isolates were commonly susceptible to β-lactam antimicrobials and exhibited a great genetic heterogeneity as determined by pulsed-field gel electrophoresis typing. The results indicate that A. viridans might be included in the list of possible etiological agents causing disease in pigs.